Then and now: the evolution of the image of nursing and nurses in Malay society (1957-2018) - Saidun, Salilah; Akhmetova, Elmira (Lincoln University College, Asia Pacific Higher Learning Sdn Bhd, 2021)
Background: The public image of nursing and nurses evolves from time to time and varies in different societies around the world. Although the issue received scholarly attention, past literary works on the issue in Malay society in Malaysia is scarce. This paper aims to bridge this gap by describing the changes in the public image of nursing and nurses in Malay society from 1957 to 2017. Method and Materials: In this qualitative study, thematic analysis of newspaper reports and interviews transcripts involving senior and retired nurses in four selected healthcare institutions in Peninsular Malaysia – who were identified through purposive and snowball sampling – were conducted. Results: The negative image of nursing as a disreputable work has improved and is now seen as a noble and rewarding profession. However, the evolution of the public image of nurses is a mixed phenomenon where nurses are now perceived to have improved intellectually but have deteriorated in terms of humanity. Conclusion: The study reveals that the image of nursing and nurses in Malaysia had evolved, with the improvement of certain aspects and deterioration in others. As the image evolves in line with the dynamics of nursing and the dynamics of the society, nurses ought to tailor the advocacy effort to improve the representation of nursing and nurses to suit the circumstances from time to time.